Closing the Care Gap: A Primer on Quality Improvement for Heart Failure Clinicians. (May 2017) - Moayedi, Yasbanoo; Schofield, Toni; Etchells, Edward; Silver, Samuel A.; Kobulnik, Jeremy; McQuillan, Rory; Bell, Chaim; Linghorne, Meredith; Ross, Heather J.
Abstract : Quality improvement (QI) initiatives have become an integral part of patient-centered care. In this primer, we outline 6 steps for initiating, implementing, and monitoring improvement in heart failure care. These steps include acknowledging that improvement is needed and setting a culture for improvement; forming a QI team; understanding the local problem; generating improvement strategies that will fit with the local problem; monitoring; testing; and refining improvements, analysis of data, and interpretation of run charts. This primer provides tools and resources for clinicians who want to learn how to perform QI specifically in the field of heart failure. We will illustrate the application of these steps using a hypothetical example for a congestive heart failure postdischarge clinic.